A Primer on Invasive Species in Coastal and Marine Waters - Charles Jacoby; Linda Walters; Shirley Baker; Karen Blyler (EDIS, 2006)
Now available online! SGEB-60, a 28-page full-color circular by Charles Jacoby, Linda Walters, Shirley Baker, and Karen Blyler, provides important background information on invasive species, especially invasive species in saltwater systems. Includes bibliography, glossary, a list of international laws and conventions related to invasive species, a directory of experts, and additional sources of information. Published by Florida Sea Grant, University of Florida IFAS Extension, July 2004.